Hydroponic Cultivation business of Lettuce (Lactuca sativa L.) at BBPP Ketindan Lawang Malang - Widiwurjani; Muhammad Farhan Firmansyah (Future Science, 2023)
The need for food such as vegetables is increasing along with the growing population. However, the high demand for lettuce is not matched by the expansion of the area of ??agricultural land, which is actually getting narrower. Utilization of narrow land in lettuce cultivation can use a hydroponic system which has become an increasingly popular choice for farmers and consumers. The research was conducted on January 2, 2023, at the Ketindan Agricultural Training Center (BBPP). Observations were made when the lettuce was 7, 14, 21 and 35 DAP (Day After Planting) with measurement parameters namely number of leaves, plant height, and farming analysis. The results of observations made on hydroponically cultivated lettuce at the age of 35 DAP had an average number of leaves of 15.74 with the highest number of leaves being 19 and the least being 14. Lettuce plants have an average height of 18.81 cm, with the highest plant being 22.5 cm and the lowest being 17 cm. the profit earned is Rp. 284,070 in each harvest. The value of hydroponic lettuce farming is profitable because the R/C ratio reaches 2.32. The growth in height of lettuce plants is directly proportional to the increase in the number of leaves of lettuce plants and the cultivation of lettuce plants that have been carried out can be categorized as profitable because the value of the R/C ratio is more than 1.